Chapter Genomes - Harb, Omar (Springer Nature, 2016)
In the last decade, the rise of affordable affordable high-throughput sequencing technologies has led to rapid advances across the biological sciences. At the time of writing, annotated reference genomes are available within most clades of eukaryotic pathogens, and including un-annotated sequences over 550 genomes are available in total. This This has greatly facilitated studies in many areas of parasitology. In addition, the volume of functional genomics data, including analysis of differential differential transcription and DNA-protein interactions, has increased exponentially. With this unprecedented increase in publicly available data, tools to search and compare datasets are also becoming ever more important. A number of database resources are available, and access to these has become fundamental for a majority of research groups. This This chapter discusses the current state of genomics research for a number of eukaryotic parasites, discussing the genome and functional genomics resources available at the time of writing and highlighting functionally important or unique aspects of the genome for each group. In addition publicly accessible database resources pertaining to eukaryotic parasites are also discussed.